2020
DOI: 10.3390/cells9081775
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature-Dependent Effectiveness of Platinum-Based Drugs Mitomycin-C and 5-FU during Hyperthermic Intraperitoneal Chemotherapy (HIPEC) in Colorectal Cancer Cell Lines

Abstract: Cytoreductive surgery (CRS) followed by hyperthermic intraperitoneal chemotherapy (HIPEC) is a treatment with curative intent for peritoneal metastasis of colorectal cancer (CRC). Currently, there is no standardized HIPEC protocol: choice of drug, perfusate temperature, and duration of treatment vary per institute. We investigated the temperature-dependent effectiveness of drugs often used in HIPEC. Methods: The effect of temperature on drug uptake, DNA damage, apoptosis, cell cycle distribution, and cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 61 publications
2
32
0
1
Order By: Relevance
“…Extensive in vitro and in vivo experiments, varying chemotherapy and cell-line, are needed to investigate the entire spectrum of thermal enhancement for each cancer origin. Substantial in vitro data, combining various chemotherapies with various cell-lines, is presented in (Helderman et al., 2020 ), underlining the variability of the thermal enhancement of chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive in vitro and in vivo experiments, varying chemotherapy and cell-line, are needed to investigate the entire spectrum of thermal enhancement for each cancer origin. Substantial in vitro data, combining various chemotherapies with various cell-lines, is presented in (Helderman et al., 2020 ), underlining the variability of the thermal enhancement of chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…However, convection in the peritoneal cavity affects the drug delivery, which was not accounted for during this study. Furthermore, the thermal effect during HIPEC is expected to play a major role in the drug delivery, since temperature influences the cytotoxicity of the chemotherapy, the diffusivity and the tumor microenvironment (Helderman et al., 2019 , 2020 ). Other treatment parameters such as dose and velocity could also influence the drug distribution in the peritoneal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The increased cytotoxicity of DOX, when administered with heat, may be attributed to modulating the tumor physiology and microenvironment, due to the increase of heat-induced membrane permeability and concomitant cellular uptake, which thus increases drug accumulation within the tumor cells (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, many of the in vitro studies that have aimed to establish thermal enhancement of chemotherapy have used temperatures, exposure times, and drug concentrations that are not clinically relevant or achievable. Helderman and coworkers recently performed a series of in vitro experiments using clinically relevant conditions (38-43 • C for 60 min) in several 2D and 3D human colorectal cancer cultures [34]. They showed that thermal enhancement of cytotoxicity is highly dependent on the cell line and on the drug used: thermal enhancement was evident for oxaliplatin and cisplatin, but not for mitomycin C, carboplatin, or 5-FU.…”
Section: Use Of Hyperthermiamentioning
confidence: 99%